(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2025)
Crisis of Representative Democracy in Latin America: Between Authoritarianisms and Constituent Democratic Movements This article examines the current crisis of representative democracy, particularly in Latin America, in the context of global challenges such as neoliberalism, authoritarianism and what economist Adam Tooze calls the “polycrisis,” a convergence of climatic, geopolitical and economic crises. Both left-wing populism, which seeks to restore centrality to the device of state sovereignty, and right-wing populist authoritarianism, which subordinates democracy to market forces, are criticized. The article argues that these approaches are limited by political patterns that reproduce processes of de-democratization. In the second part, the analysis will shift to the democratic renewal proposed by Latin American social movements: the recent social uprisings in Chile, Colombia and Argentina. We will focus on the transformation of the social and political composition of these movements as well as on the new forms of organization and claims that increasingly exceed the modern legal and state form.